Primary Segmental Colonic Tuberculosis: A Case Report - Haque, MM; Siddique, AB; Badruddoza, SM; Amin, MR; Rahman, MG; Hasan, MZ; Abedin, MJ; Islam, M Takbirul (TAJ: Journal of Teachers Association, 2009)
Tuberculosis is known to involve any segment of gastrointestinal tract. While tuberculosis of the small bowel is common, isolated primary tuberculosis of the large bowel is quite uncommon. We report two cases of isolated colonic tuberculosis, successfully treated with primary resection. doi: 10.3329/taj.v17i1.3491 TAJ 2004; 17(1) : 52-54